NATURE OF THE CRUST IN THE LAXMI BASIN (14°-20°N), WESTERN CONTINENTAL MARGIN OF INDIA - Krishna K.S.; Gopala Rao D.; Sar D. (My University, 2006)
The nature of the crust in the Laxmi Basin, western margin of India is an uncertain issue; more importantly this has implications on paleo-geographic reconstructions of the western Indian Ocean. We have analysed three geophysical datasets and modelled gravity and magnetic anomalies for determining nature of the crust. Basement of the Laxmi Basin includes numerous highs, which make the basement uneven and shallower compared to the Western Basin. The Laxmi Basin is characterised by a broad gravity high and a narrower prominent gravity low within it, while within the basin the broad anomaly gradually increases towards north. The Panikkar Ridge is associated with the gravity low, which is comparable, at least in sign, to known negative gravity anomaly of Laxmi Ridge. Intrusive structures mapped in the Laxmi Basin coincide with significant magnetic anomalies, which were earlier interpreted as seafloor-spreading anomalies. Model studies reveal that the Laxmi Basin consists of ~14 km thick stretched continental crust, in which magmatic bodies have been emplaced, whereas Panikkar Ridge remains less altered stretched continental crust. The crust of the Laxmi Basin is mostly thinner than crust under Laxmi Ridge and continental margin. In addition to the rift-drift related stretching of the continental margin the Laxmi Basin possibly has undergone extra stretching in E-W direction during the pre-Tertiary period. At ~68 Ma Deccan volcanism on western India may have disrupted the initial conditions that were leading to onset of spreading in the basin.